Risk-benefit assessment of cereal-based foods: a case study under RiskBenefit4EU project - Martins, Carla (2021)
Cereal-based foods, including breakfast cereals (BC) and infant cereals (IC), are among the first solid foods introduced in infants’ diets. BC and IC are sources of nutrients that have beneficial effects on health. However, they can also be a source of potentially harmful chemical or microbiological contaminants, or of nutrients that at high consumption levels may lead to adverse health effects. Young children have a less varied diet and consume food in amounts that are higher relative to their body weight, if compared to adults. Therefore, the potential health risk of contaminants in foods consumed by young children is likewise higher. The aim of this study was to assess the risks and benefits associated with the consumption of BC and IC in children below 35 months of age in Portugal. The health effects associated with the presence of aflatoxins, Bacillus cereus, sodium and free sugars were weighted against the health benefits of the intake of fiber. A risk-benefit assessment approach was applied and the impact on health of a modification in consumption of BC and IC from the current consumption to various alternative scenarios was quantified in terms of disability-adjusted life years. Results showed that moving from the current consumption to the considered alternative scenarios could result in a gain of healthy-life years. The Portuguese children could benefit from exclusive BC consumption if the products consumed have an adequate nutritional profile in terms of fiber, sodium and free sugars and levels of aflatoxins reduced as much as possible.